2011
DOI: 10.1111/j.1365-2435.2011.01851.x
|View full text |Cite
|
Sign up to set email alerts
|

Sun and shade leaves of Olea europaea respond differently to plant size, light availability and genetic variation

Abstract: Summary1. Canopy plasticity, the expression of different leaf phenotypes within the crown of an individual tree has complex functional and evolutionary implications that remain to be thoroughly assessed. We hypothesized that it can lead to disparity in how leaves in different positions of the canopy change with allometric growth and population genetic structure. 2. Leaf phenotypes of the inner and outer canopy were estimated using eight morphological and physiological characters. All traits were measured under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 53 publications
0
30
1
3
Order By: Relevance
“…Leaf size and shape are not solely determined by genetic variability but also change during development and adapt to environmental conditions (Sultan, 1995(Sultan, , 2000Cho et al, 2007;Bar and Ori, 2014). Phenotypic plasticity of leaf morphology helps plants to optimize sunlight harvesting, CO 2 gas exchange, and acclimatization to changing ambient temperatures (Nicotra et al, 2010;de Casas et al, 2011). Hence, understanding the cellular and molecular mechanisms of growth regulation is of central importance to improve plant yield, quality, and resource use efficiency.…”
mentioning
confidence: 99%
“…Leaf size and shape are not solely determined by genetic variability but also change during development and adapt to environmental conditions (Sultan, 1995(Sultan, , 2000Cho et al, 2007;Bar and Ori, 2014). Phenotypic plasticity of leaf morphology helps plants to optimize sunlight harvesting, CO 2 gas exchange, and acclimatization to changing ambient temperatures (Nicotra et al, 2010;de Casas et al, 2011). Hence, understanding the cellular and molecular mechanisms of growth regulation is of central importance to improve plant yield, quality, and resource use efficiency.…”
mentioning
confidence: 99%
“…Shading treatment reduces the PAR (photosynthetically active radiation) for intercrops and changes the microclimate under the canopy, resulting in decreased photosynthesis and transpiration rates. However, the intercrops can adapt to the low light intensity with changes in chlorophyll and the intercellular CO 2 concentration [24][25][26]. The physiological characteristics and productivity of intercrops impacted by the changed microclimate need further investigation [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, the canopy shading reduces the net photosynthetic rate of the leaves, as well as the initial light energy conversion rate of PSII, so that the photosynthesis of vegetable is affected [24]. Studies have shown that leaves become thinner, leaf area becomes larger, and stem height increases in shading conditions in order to improve the ability to absorb and capture light [25,26]. At the same time, the leaves absorb more light, which causes the chlorophyll a/chlorophyll b to decrease and the pore density to decrease.…”
Section: Introductionmentioning
confidence: 99%
“…Because of being more exposed to excessive light, outer layers of the canopy suffer more drastic changes in the abiotic conditions than inner layers (Niinemets 2007). Plant leaves show different ecophysiological traits at different positions in the canopy (Casas et al 2011;Giorio & Nuzzo 2012). Without these structural protections, photoinhibition of photosynthesis is likely to be much greater, which leads to apparent reduction of daily carbon gain (Pearcy et al 2005).…”
Section: Introductionmentioning
confidence: 99%